1993
DOI: 10.1111/j.1574-6968.1993.tb06019.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphate-dependent enzymes in some coryneform bacteria isolated from sewage sludge

Abstract: Eleven isolates obtained from a laboratory sewage treatment plant, most of them presumptively assigned to the coryneform genera Curtobacterium and Aureobacterium were studied for the presence of intracellular polyphosphates and polyphosphate dependent enzymes. All isolates stored polyphosphates and showed adenylate kinase activities ranging from 64 to 815 mU mg -1. Polyphosphate:AMP phosphotransferase could only be detected in one isolate. Three isolates showed a polyphosphate kinase activity also in minor amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 21 publications
1
4
0
1
Order By: Relevance
“…Other researchers also found that actinobacteria comprised a large proportion of bacteria in EBPR sludge, as determined by FISH (29,51), by respiratory quinone profiles (27), and by clone library analysis (17). Additionally, a range of actinobacterial isolates has been investigated for phosphate accumulation (6,39,40,48). It will be worthwhile to follow up on the role of actinobacteria in EBPR.…”
Section: Discussionmentioning
confidence: 97%
“…Other researchers also found that actinobacteria comprised a large proportion of bacteria in EBPR sludge, as determined by FISH (29,51), by respiratory quinone profiles (27), and by clone library analysis (17). Additionally, a range of actinobacterial isolates has been investigated for phosphate accumulation (6,39,40,48). It will be worthwhile to follow up on the role of actinobacteria in EBPR.…”
Section: Discussionmentioning
confidence: 97%
“…This indicates that at least two kinds of NAD kinase, poly( P )/ATP–NAD kinase and ATP–NAD kinase, exist in living organisms. Other NAD‐phosphorylating enzymes which utilize p ‐nitrophenylphosphate or glucose 6‐phosphate have been detected in cell extracts of Proteus mirabilis [11] and coryneform bacteria isolated from sewage sludge [17], respectively. E. coli ATP–NAD kinase, as well as poly( P )/ATP–NAD kinase [7], did not show any activity toward these phosphoryl donors.…”
Section: Discussionmentioning
confidence: 99%
“…Although some of the isolates were shown to store polyphosphate to a certain extent, a polyphosphate-dependent enzyme system, as reported for Acinetobacter [7,8,33] could not be detected (unpublished results).…”
Section: The Role Of Acinetobacter and Aeromonas In Epr Treatment Plamentioning
confidence: 90%
“…Different Grampositive organisms have already been described in the literature [44,46] showing high amounts of P accumulation. Recently, additional polyphosphate-dependent enzymes were found in coryneform bacteria isolated from sewage sludge [8], which is additional evidence for the importance of Gram-positive bacteria with a high G+C content as P-removing organisms.…”
Section: The Role Of Acinetobacter and Aeromonas In Epr Treatment Plamentioning
confidence: 99%